2008
DOI: 10.1007/s10764-008-9309-y
|View full text |Cite
|
Sign up to set email alerts
|

Social Relationships Among Male Alouatta pigra

Abstract: We investigated male social relationships in 2 groups of black howlers (Alouatta pigra) in Palenque National Park, Mexico, over a 14-mo study characterized by frequent changes in male group membership. Both single males and pairs of males entered our focal groups. Single males tended to join groups, whereas pairs of males entering groups together successfully evicted resident males. The 19 male dyads across the 11 periods defined by changes in group membership were rarely in close proximity or interacting with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 49 publications
0
37
0
2
Order By: Relevance
“…Behavioral data were collected using 30 min focal animal samples on both adult males and females. In addition, instantaneous scan samples were carried out at 10-min intervals throughout the focal animal samples to record the identities of all adult neighbors within a 5 m radius of the focal individual (Van Belle et al 2008, 2009a. Data on the male takeover and infanticide events and on sexual interactions were collected ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral data were collected using 30 min focal animal samples on both adult males and females. In addition, instantaneous scan samples were carried out at 10-min intervals throughout the focal animal samples to record the identities of all adult neighbors within a 5 m radius of the focal individual (Van Belle et al 2008, 2009a. Data on the male takeover and infanticide events and on sexual interactions were collected ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed in A. caraya 0.019 int/ind/hr [Bicca-Marques, 1993], and in A. palliata; male-male ¼ 0.018 int/ind/hr, male-female ¼ 0.049 int/ind/hr [Wang & Milton, 2003]. The low level of agonistic interactions is possibly related to the high costs imposed by physical aggression that may result in the death of males [Dias et al, 2010], thus, the predominant behaviors in male-male howler relationships involve low physical risk [Dias et al, 2008;Garber & Kowalewksi, 2011;Preuschoft & van Schaik, 2000;van Belle et al, 2008;Wang & Milton, 2003]. Nevertheless, intense forms of aggression have been reported for howlers (Alouatta arctoidea [Crockett & Pope, 1988], A. palliatta [Cristóbal-Azkarate et al, 2004;Dias et al, 2010]).…”
Section: Dominance and Relatednessmentioning
confidence: 99%
“…This weak stability of male's position in the hierarchy and its relationship with female fertilization results in males needing to escalate towards the central position within a multimale group. In other species of howlers, such as A. pigra, several changes in male group membership over a relatively short period of time have been observed (seven changes in 6 months [van Belle et al, 2008]). Changes in male group membership sometimes escalated to physical aggression, causing bloody and lethal wounds involving high potential costs for both males [Horwich et al, 2000;van Belle et al, 2008].…”
Section: Molecular Determination Of Paternitymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, comparisons of methods for collecting activity and diet data are rare in the primate literature in general [Dunbar, 1976;Rhine and Flanigon, 1978;Rhine and Ender, 1983;Bernstein, 1991;Fragaszy et al, 1992;Kawanaka, 1996;Zinner et al, 1997;Rose, 2000;Stevenson and Quinones, 2004;Hernández-Lloreda and Colmenares, 2006;Edwards et al, 2010;Gilby et al, 2010], and studies comparing methods for describing spatial proximity patterns among individuals are completely absent (but see Haddadi et al [2011] for a discussion on temporal and spatial criteria for accurately constructing social networks). Because data describing interindividual relationships may depend heavily on proximity data, especially in primates with low frequencies of social interaction [Di Fiore and Fleischer, 2005;Van Belle et al, 2008;Takuda et al, 2012], a thorough understanding of the techniques available for estimating spatial relationships among primate individuals is critical. Without systematic comparisons of these techniques, such an understanding is impossible.…”
Section: Introductionmentioning
confidence: 99%